The Transition to a State Medical Service
1942-08 1942 1940s 8 pages (K) GENERAL PRACTITIONER SERVICE (59) The benefits of this service will be available without charge to all residents in Great Britain, without any income limit. It is to be expected that a limited class (represented by those who now send their children to private schools) will refrain from using the State Medical Service, but will prefer to employ such independent practitioners as may have chosen to remain outside the State Service, where any such are available. This does not imply that the State Service will be anything but greatly superior to anything which an independent practitioner can supply, but all sensible persons must recognise that there are some doctors and some patients who may prefer complete independence of action at whatever price. Nothing would be gained by seeking to control or prevent such practice. (60) Patients like or dislike particular doctors for a great variety of reasons, most of which have very little to do with the skill which the doctor places at their service. Nevertheless, the offer of free service proves quite enough to persuade them to accept with complacency, if not with gratitude, the service of any doctor who chances to turn up at the local clinic. In populous districts it may be possible to allow free choice, so long as this does not mean that one doctor is overworked while another has insufficient occupation. In other districts no choice may be possible. The Union therefore maintains that free choice of doctor should be provided as far as possible amongst the doctors in the Service, but realises that it will of necessity be limited in extent. There is a widespread feeling that control by the State might not be able to prevent overworking of the popular doctor while his less acceptable colleague, earning the same salary, would do insufficient to deserve it. The Union does not claim that any organisation can overcome the fundamental defects of human nature, but it has no doubt whatever that a State Service can and will protect any doctor, however popular, from the gross overwork which has been his lot under the present competitive system. It can also find effectual means of dealing with those who do not pull their full weight in the team. (61) When the new system comes into operation all doctors of whatever age who are actually in practice must be given an opportunity to join it. This will include those released from the Forces. (62) Newly registered practitioners who were not qualified at the inception of the Service must be given opportunities to join. (63) Both men and women Medical Officers will be required and must be offered the same terms. The single or married status of women Medical Officers will not of itself affect their conditions of service, which will depend entirely upon the efficient performance of the duties which their position in the Service requires of them. Adequate periods of leave will be given before and after childbirth. (64) The position of the doctor who is actually in practice when the Service comes into being but who is over the retiring age of the Service, has given rise to several questions. It is governed by the statement already made that all doctors actually in practice will then be given an opportunity to join the Service. Such practitioners would, no doubt, be asked to resign as soon as their compensation and pensions had been settled, but it does not appear that any particular hardship would thus be imposed upon them. (65) Those who enter the Service at its inception, and can show that they have already formed substantial professional and social connections in the area in which they are practising, must not be asked to remove to a new area. Those who have not previously been in general practice will have choice of districts according to their qualifications. These qualifications will include academic distinction, knowledge of particular types of practice, or of particular areas, and age at entrance. Thus a doctor who has been brought up in the country and has a sympathetic knowledge of rural life will find that his claim to be posted to a rural district and, perhaps, to the area in which his father practised would receive careful consideration. On the other hand, a doctor who had special surgical experience would be likely to find himself sent to some area in which a small hospital would give him a chance to combine general practice with responsible surgical work. (66) The particular needs and wishes of more elderly doctors — e.g., new entrants who had retired from the military services — would be met as far as possible by allotting them to posts in which no undue call would be imposed upon their strength. These are only examples of the adjustments which will be required in the broad interests of good service. It will also be necessary to allow transfers from one area to another where a doctor's choice or the needs of the Service make this desirable. (67) In the early days of the Service it will, undoubtedly, be necessary to increase the medical population of industrial areas, while residents in high-class residential areas will find that there are fewer doctors available than hitherto. In epidemic periods temporary transfers will be necessary, and it is possible that some doctors may prefer to spend most of their time as locums. All vacancies in the service, whether for posts requiring special skill or otherwise, must be advertised so that all members of the Service shall have an equal chance to apply for them, and arrangements will be made to permit of transfer from the Home Treatment side of the Service to administrative and specialist branches, and vice versa. Transfer to specialist branches will usually be preceded by opportunities to practise the particular speciality, as a clinical assistant or otherwise, and such opportunities must be open to all, so far as administrative arrangements will permit. (L) TERMS OF SERVICE (68) Service must be whole time, i.e., no private practice will be allowed. Those members of the public who dislike the idea of taking advantage of a free service, but whose own doctors have joined the State Service, will have either to find a new doctor or to overcome their dislikes. Many of the personal service duties now undertaken by whole-time municipal officers, e.g., inspection of school children, clinic work, and diphtheria immunisation, will be undertaken by general practitioners. Except in rural districts, practice will be conducted from a central office at which all messages will be received, and the doctor's private house will be as much his castle as the house of any other Civil Servant. (69) Adequate holidays, study leave, sick leave, etc., must, of course, be an essential part of the conditions of service. Compensation for injury or illness acquired in the Service will be included. 7 292/847/1/4